A standardized rat burr hole defect model to study maxillofacial bone regeneration. (1st March 2019) - Liu, Guanqi; Guo, Yuanlong; Zhang, Linjun; Wang, Xiaoshuang; Liu, Runheng; Huang, Peina; Xiao, Yin; Chen, Zhuofan; Chen, Zetao
Graphical abstract: Abstract: With high incidence rate and unique regeneration features, maxillofacial burr hole bone defects require a specially designed bone defect animal model for the evaluation of related bone regenerative approaches. Although some burr hole defect models have been developed in long bones or calvarial bones, the mandible has unique tissue development origins and regenerative environments. This suggests that the defect model should be prepared in the maxillofacial bone area. After dissecting the anatomic structures of rat mandibles, we found that creating defects in the anterior tooth area avoided damaging important organs and improved animal welfare. Furthermore, the available bone volume at the anterior tooth area was superior to that of the posterior tooth and ascending ramus areas. We then managed to standardize the model by controlling the age, weight and gender of the animal, creating standardized measurement instruments and reducing the variations derived from various operators. We also succeeded in deterring the self-rehabilitation of the proposed model by increasing the defect size. The 6 × 2 mm and 8 × 2 mm defects were found to meet the requirements of bone regenerative studies. This study provided a step-by-step standardized burr hole bone defect model with minimal tissue damage in small animals. The evaluations resulting from this model testify to the in vitro outcomes of the proposed regenerative approaches and provide preliminary screening data for further large animal and clinical trials. Therefore, the inclusion of this model may optimize the evaluation systems for maxillofacial burr hole bone defect regenerative approaches. Statement of Significance: Unremitting effort has been devoted to the development of bone regenerative materials to restore maxillofacial burr hole bone defects because of their high clinical incidence rate. In the development of these biomaterials, in vivo testing in small animals is necessary to evaluate the effects of candidate biomaterials. However, little has been done to develop such defect models in small animals. In this study, we developed a standardized rat mandible burr hole bone defect model with minimal injury to the animals. A detailed description and supplementary video were provided to guide the preparation. The development of this model optimizes the maxillofacial bone regenerative approach evaluation system.